Learning from higher arts education in designing constructivist learning spaces: a case study of inQbate: the centre of excellence in teaching and learning in - Hamilton,T; Morris,R; Childs,PRN (Burlington Press, 2007)
The aims of ‘InQbate: The Centre of Excellence in Teaching and Learning in Creativity’ aretwofold: to increase the creativity of our teaching, and to improve our teaching of creativity [Childset al, 2006]. This case study outlines how we have addressed these twin goals by drawing on theexperience of the creative disciplines in order to design physical learning spaces that supportcreation-, construction-, performance-, installation- and exhibition-based activities within a socialconstructivist pedagogical model. We hope that this will act as a bridge for increased dialogueand collaboration between Higher Arts Education and non-Arts subjects.